Regulation of testosterone degradation in Comamonas testosteroni (2008)
Recently, we have identified a gene encoding a LuxR-type factor, TeiR (Testosterone-inducible Regulator), which positively regulates steroid degradation in Comamonas testosteroni. Herein, we demonstrate that TeiR interacts in vivo with steroid catabolic gene promoters. The presence of testosterone induces a significant TeiR protein increase at the early logarithmic phase of growth. Interestingly, it is not until the early stationary phase where the activation of a steroid-inducible gene promoter is observed, indicating that testosterone might not be the true inductor of the steroid degradation pathway. In addition, ?-galactosidase expression driven by a testosterone-inducible promoter is prematurely activated in cells cultured in medium supplemented with ethyl acetate extracts obtained from the early stationary phase cell-free supernatants of C. testosteroni grown in presence of testosterone. Complementation experiments of C. testosteroni wild type performed with teiR deletion constructs indicate that extra-copies of deleted-TeiR exert a dominant negative effect on the wild-type TeiR protein. While, when C. testosteroni teiR mutants were used to carry out complementation assays only the full length gene can overcome the teiR mutant phenotype. Altogether these findings indicate that TeiR regulates steroid catabolic genes interacting with their promoters and suggest that this interaction requires the presence of a testosterone-derived metabolite to induce the system.